Swertia chirayita: The Himalayan Herb - Khanal, Supreet; Shakya, N.; Nepal, N.; Pant, D. (International Journal of Applied Sciences and Biotechnology, 2014)
Swertia chirayita is a native Himalayan herb typically found in the altitude of 1500 to 3100m. Swertia species are commonly used as primary medicines in fever, digestive and enteric diseases; especially S. chirayita is of principal importance. The pharmacological and ethno-medicinal perspective of the plant is well understood traditionally and pharmaceutically. Its secondary metabolites including glycosides and xanthones show promising bioactivity making it a powerful herb. Mixing of Swertia chirayita with its other species is done routinely in chiretta trade. Extensive wild collection and lack of sustainable conservation has led to the vulnerable status of the wild cultivar. DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11281 Int J Appl Sci Biotechnol, Vol. 2(4): 389-392